2007
DOI: 10.1111/j.1467-2679.2007.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Marine extinctions revisited

Abstract: In recent years, more than 130 extinctions have been estimated to have occurred in the marine realm. Here we review this body of evidence and show that this figure may actually be overestimated by as much as 50%. We argue that previous estimates have not fully taken into account critical uncertainties such as naturally variable geographical distributions, and have misinterpreted documentary evidence. However, current evidence indicates that some sharks, rays and reef‐associated species, although not necessaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 63 publications
(99 reference statements)
4
37
0
Order By: Relevance
“…Fishing has caused reductions in abundances of many fish stocks (Worm et al. 2009) and extirpations of a few species from LME-scale regions (Dulvy, Sadovy & Reynolds, 2003; Wonham & Carlton, 2005; del Monte-Luna et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fishing has caused reductions in abundances of many fish stocks (Worm et al. 2009) and extirpations of a few species from LME-scale regions (Dulvy, Sadovy & Reynolds, 2003; Wonham & Carlton, 2005; del Monte-Luna et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the last known date of occurrence is provided together with a reason for the loss. Although some extinctions are certain, others are debated and there are examples of species believed to be extinct that have been rediscovered later on, or locally extirpated species that have recolonized an area after decades of absence [30].…”
Section: Historical Recordmentioning
confidence: 99%
“…Dulvy et al [11] reported 133 marine extirpations and extinctions (Figure 2b), most of them local extirpations during the 19th and 20th centuries. Although some of these have been disputed [30], others have been confirmed or added [20,31]. Moreover, historical assessments of estuaries, coastal seas, and coral reef ecosystems worldwide show dramatic declines in the abundance of many species over past decades and centuries [32,33].…”
Section: Historical Extinctions and Extirpationsmentioning
confidence: 99%
“…Complete disappearance of a species from a basin as wide as the Mediterranean in a few decades is perhaps unrealistic, and represents a highly debated issue (Bianchi et al 2012). Examples do exist, however, of local extinctions or severe decrease of certain species (del Monte-Luna et al 2007). The commercial sponge Spongia officinalis Linnaeus, 1759, for instance, has been dramatically reduced in the last decades due to overexploitation and disease (Pronzato & Manconi 2008;Voultsiadou et al 2011).…”
Section: Introductionmentioning
confidence: 97%
“…This notwithstanding, extinction risk in the sea is still little understood (Roberts & Hawkins 1999;del Monte-Luna et al 2007).…”
Section: Introductionmentioning
confidence: 97%